In Silico Structural and Functional Characterization of the RSUME Splice Variants - Gerez, J. (2013)
RSUME (RWD-containing SUMO Enhancer) is a small protein that increases SUMO conjugation to proteins. To date, four splice variants that codify three RSUME isoforms have been described, which differ in their C-terminal end. Comparing the structure of the RSUME isoforms we found that, in addition to the previously described RWD domain in the N-terminal, all these RSUME variants also contain an intermediate domain. Only the longest RSUME isoform presents a C-terminal domain that is absent in the others. Given these differences, we used the shortest and longest RSUME variants for comparative studies. We found that the C-terminal domain is dispensable for the SUMO-conjugation enhancer properties of RSUME. We also demonstrate that these two RSUME variants are equally induced by hypoxia. The NF-κB signaling pathway is inhibited and the HIF-1 pathway is increased more efficiently by the longest RSUME, by means of a greater physical interaction of RSUME267 with the target proteins. In addition, the mRNA and protein levels of these isoforms differ in human glioma samples; while the shortest RSUME isoform is expressed in all the tumors analyzed, the longest variant is expressed in most but not all of them. The results presented here show a degree of redundancy of the RSUME variants on the SUMO pathway. However, the increased inhibition conferred by RSUME267 over the NF-κB signaling pathway, the increased activation over the HIF-1 pathway and the different expression of the RSUME isoforms suggest specific roles for each RSUME isoform which may be relevant in certain types of brain tumors that express RSUME, like human pituitary adenomas and gliomas. © 2013 Gerez et al.